2022
DOI: 10.3390/cells11203234
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Neurogenesis in the Adult Hippocampus Using Antidepressants and Mesenchymal Stem Cells

Abstract: The hippocampus is one of the few privileged regions (neural stem cell niche) of the brain, where neural stem cells differentiate into new neurons throughout adulthood. However, dysregulation of hippocampal neurogenesis with aging, injury, depression and neurodegenerative disease leads to debilitating cognitive impacts. These debilitating symptoms deteriorate the quality of life in the afflicted individuals. Impaired hippocampal neurogenesis is especially difficult to rescue with increasing age and neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 226 publications
0
2
0
Order By: Relevance
“…Mood stabilizers such as lithium, antidepressants (e.g. selective serotonin reuptake inhibitors [SSRIs]), and electroconvulsive therapy, increase adult hippocampal neurogenesis [11,12,13,14,15,16]. In our study, signi cant volumetric changes were observed in the hippocampal left DG-head and left DG-total in the BL group but not in the DL group.…”
Section: Effect Of Light On Clinical Symptomsmentioning
confidence: 56%
“…Mood stabilizers such as lithium, antidepressants (e.g. selective serotonin reuptake inhibitors [SSRIs]), and electroconvulsive therapy, increase adult hippocampal neurogenesis [11,12,13,14,15,16]. In our study, signi cant volumetric changes were observed in the hippocampal left DG-head and left DG-total in the BL group but not in the DL group.…”
Section: Effect Of Light On Clinical Symptomsmentioning
confidence: 56%
“…Dysfunction of the hippocampus due to aging, injury, depression, or neurodegenerative diseases can lead to cognitive decline, significantly affecting the quality of life for individuals. Antidepressant treatments hold promise in directly or indirectly promoting AHN and alleviating depressive symptoms ( Kot et al, 2022 ). SSRIs, commonly prescribed antidepressants, exert their effects by selectively blocking the reuptake of 5-HT, thereby prolonging and enhancing its activity ( Perez-Caballero et al, 2014 ; Bi et al, 2022 ).…”
Section: Pathological Connection Between Ahn and Mddmentioning
confidence: 99%